2007
DOI: 10.1111/j.1440-1789.2007.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal dysembryoplastic neuroepithelial tumor with signs of atypia after regrowth

Abstract: We report the case of a multifocal dysembryoplastic neuroepithelial tumor (DNT) in a 7-year-old girl with local tumor regrowth 6 years later. The tumor was localized in the right parietal lobe extending from the cortex into the periventricular white matter. After subtotal resection of a histopathologically confirmed DNT we observed unexpected tumor progression in long-term follow-up. Therefore, a second surgery was performed when the patient was 14 years of age. In neuropathological examination of the second s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…One paper has expressed doubts as to the neoplastic basis of DNET [5], considering it to represent a hamartomatous anomaly with abnormal arrangements of normal neuronal and glial components. This is not a widely recognized perspective, with cases of malignant transformation [6, 7] and regrowth following subtotal resection [8] supporting the hypothesis that it is a true neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…One paper has expressed doubts as to the neoplastic basis of DNET [5], considering it to represent a hamartomatous anomaly with abnormal arrangements of normal neuronal and glial components. This is not a widely recognized perspective, with cases of malignant transformation [6, 7] and regrowth following subtotal resection [8] supporting the hypothesis that it is a true neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Those with multifocal involvement are rare, with only four cases reported in which DNETs occurred in infra-and supra-tentorial locations (Leung et al, 1994;Krossnes et al, 2005;Schittenhelm et al, 2007;White et al, 2011). Typically located in the temporal lobes, DNETs have also been reported within the periventricular white matter, basal ganglia, thalamus, brainstem, and cere-bellum.…”
mentioning
confidence: 99%
“…16 Some aggressiveness criteria, including obvious mitotic figures, increased cellularity and nuclear pleomorphism, significant microvascular proliferation, elevated proliferative activity, and focal leptomeningeal involvement can be observed in a few cases and suggested that these patients need to be more closely followed up. 1,5,17,18 In this study, 1 case (case 3) with increased cellularity and microvascular proliferation and another (case 7) with isolated foci of leptomeningeal involvement and elevated proliferative activity (MIB1 index focally up to 3.6%) developed a recurrence of seizures. The impact of these aggressiveness criteria on patients' long-term outcomes remains to be further studied.…”
Section: Discussionmentioning
confidence: 89%